TAKARAN DOSIS LUMPUR SAWIT DAN PUPUK KCL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L) PADA ULTISOLS DI BENGKULU - Bilman Wilman Simanihuruk; Yanti Oktavia Lumbantoruan; Herry Gusmara (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[APPLICATION OF PALM OIL SLUDGE DOSE AND KCl FERTILIZER AGAINST GROWTH AND YIELD OF CORN (Zea mays L) ON ULTISOLS IN BENGKULU]. This study aims to determine the dose of palm oil sludge (POS) and the optimal dose of KCl fertilizer to the growth and yield of corn. The study was conducted from June to October 2018. The design used is Randomized Completely Block Design (RCBD) which is arranged in factorial with two treatment factors. The first factor is the POS consisting of 3 levels: 0 tons/ha, 10 tons/ha, and 20 tons/ha. The second factor is the dose of KCl fertilizer consisting of 3 levels: 0 kg/ha, 100 kg/ha, and 200 kg/ha. The results showed no real influence on the combination of POS and KCl fertilizer treatment on the growth and yield of corn. The 10 tons/ha POS dose delivers the best results on the entire observation variable. KCl fertilizer indicates a different effect is not noticeable on all observed variables.